2014
DOI: 10.1519/jpt.0b013e3182abe7cb
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Fall Risk Assessment Tool That Is Specific to Physical Function Predicts Falls in Community-Dwelling Elderly People

Abstract: These findings may contribute to earlier identification of high-risk fallers and intervention for fall prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…20–30 min) and more conveniently. 13 , 14 , 15 TUGT has been widely used in the balance test with the cutoff point for risk of falls ranging from 11.0 to 12.3 s 16 , 17 , 18 ; however, its predictive power is highly limited to a high-functioning population. 19 Regarding the CDP, the SOT protocol could be used to differentiate elderly non-fallers from fallers due to balance impairment, 20 and it appears to be more sensitive in identifying those at a high-risk of recurrent falls, compared with clinical tests, especially in condition 5 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…20–30 min) and more conveniently. 13 , 14 , 15 TUGT has been widely used in the balance test with the cutoff point for risk of falls ranging from 11.0 to 12.3 s 16 , 17 , 18 ; however, its predictive power is highly limited to a high-functioning population. 19 Regarding the CDP, the SOT protocol could be used to differentiate elderly non-fallers from fallers due to balance impairment, 20 and it appears to be more sensitive in identifying those at a high-risk of recurrent falls, compared with clinical tests, especially in condition 5 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 49 FRATs were identified to be included in the review. Of the 49 tools identified, six were excluded as the researchers were unable to obtain them (Jester et al, 2005; Hirase et al, 2014;Miyakoshi et al, 2014), despite contacting the corresponding authors of each article in which the tools were mentioned. The 43 FRATs included in the review were analysed by the first author (HdC) and the items in each tool were identified and extracted via Microsoft® Office Excel.…”
Section: Discussionmentioning
confidence: 99%
“…This test is widely used in the elderly as a simple test (40,41,42,43,44,45) and in physical performance batteries (46) , for indirect measurement of muscle resistance of the knee joint -mainly quadriceps. The CS-5 has been demonstrated to be a simple and viable physical performance to request a decrease in daily living activity (ADL) and falls in the elderly (47,48,49) .…”
Section: Discussionmentioning
confidence: 99%